Pendugaan Umur Simpan Buah Melon (Cucumis melo L.) Terolah Minimal menggunakan Metode ASLT (Accelerated Shelf Life Test) Model Arrhenius - Sukesi, Rina; Syska, Kavadya; Nurhayati, Asti Dewi (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2023)
Melon (Cucumis melo L.) minimal processing has become an increasingly sought-after product in the fruit-based food industry. Minimally processed products offer advantages in preserving the sensory and nutritional qualities of the fruit while minimizing the use of preservatives and heat treatments that can affect the fruit's characteristics. The objective of this research is to determine the changes in the quality of minimally processed melon using the Accelerated Shelf Life Test (ASLT) method with the Arrhenius model and to determine the shelf life of minimally processed melon using the ASLT method with the Arrhenius model. The research employed the ASLTmethod with a Completely Randomized Design (CRD) consisting of 2 factors. Factor 1 involved three types of packaging (A), and factor 2 encompassed two room storage temperatures (S). The treatments in this experimental design included storage temperatures (S) of 30°C and 10°C. The results of the research indicated that the highest weight loss occurred in the sample (treatment at 10°C with wrapping packaging), while the lowest weight loss was observed in the treatment at 10°C with PP packaging. At a temperature of 30°C, melons stored in wrapping packaging for one day exhibited the highest weight loss at 96%, whereas melons stored in PP packaging for 9 days had the lowest weight loss at 54.3%. The highest soluble solids content at a storage temperature of 10°C was found in wrapping packaging, reaching 11.25% Brix, while the lowest total soluble solids content was in HDPE packaging, at 7% Brix, with a storage duration of 9 days. Observations on melons showed that the highest soluble solids content at a storage temperature of 30°C was in wrapping packaging, at 8.4%, after one day of storage, while the lowest value was in PP packaging, at 0.3%, after 9 days of storage. This research serves as a foundation for the development of more efficient storage management strategies, ensuring optimal quality of minimally processed melons during distribution and consumption.